Applying Trial Emulation Methods to Population-Scale Linked Electronic Health Records for Individuals with Multiple Long-Term Conditions Whilst Adjusting for Informative Observations - Keith Abrams; James Rafferty; Jane Lyons; Ronan Lyons; Rhiannon Owen (International Journal of Population Data Science, 2024)
Background & Objectives Trial Emulation methods can be applied to Population-Scale Linked Electronic Health Records (EHR) to generalise the results of Randomised Controlled Trials (RCTs) to a broader patient population. However, the Data Generating Mechanisms (DGMs) associated with EHR data mean that there is a need to adjust for informative observations, i.e. worse prognosis patients may have more observations.